THE EFFECTS OF FUNGAL MEDIUM ON HATCHING RATE OF BITING MIDGE - Jui-Yu Chou; Hung-Wei Chen; Chung-Chi Lin; Yu-Der Wen; Wei-Lung Wang (European Scientific Journal, ESJ, 2015)
The little black mosquitos, Forcipomyia taiwana, bite human and become one of the most annoying pests in Taiwan. Recently, the population of F. taiwana increases and invades urban and countryside. In order to effectively prevent the harassment of F. taiwana, develop control strategy is urgent and necessary. Our study found that the fungal medium influenced the length and width of the F. taiwana eggs. It also significantly decreased the hatching rate of F. taiwana. Besides, this artificial diet was more non-toxic and environment-friendly than general chemical pesticides. Thus, this study provided critical information to develop potentially useful bait of F. taiwana in the future.